Research on thermal resistance network model of concentric annular heat pipe heat for the sensor thermal protection - Jiazhi Sun; Lixin Yang; Jianjun Zhou (Case Studies in Thermal Engineering)
A concentric annular heat pipe is designed for the thermal protection of infrared sensors in high-temperature environments. A key to thermal protection is the rapid analysis of the heat pipe's heat transfer characteristics, particularly in calculating thermal resistance and temperature, which remains challenging. To address this issue, a network model considering various structural and operational conditions is developed based on the CAHP heat transfer process and network theory. The model's accuracy is validated through experiments, and the effects of filling ratio, wick structure, and installation angle are analyzed. Model analysis results indicate that the thermal resistance is higher when the working liquid is in the wick, but the evaporator's circumferential temperature distribution is uniform. As the filling ratio increases, the vapor chamber transitions into a top gas and bottom liquid state. This leads to an increase in the temperature difference between the top and bottom regions of the evaporator and condenser. The heat pipes' thermal resistance with circumferential grid wick (CGW) is lower than that of circumferential uniform wick (CUW). However, there is a significant temperature difference between the CGW's wick-chamber region. When the evaporator is positioned below the condenser, the thermal resistance is lower, and temperature difference between the top and bottom regions of the evaporator and condenser is smaller. This study can provide theoretical guidance for the CAHP's structural design and sensor placement.